2015
DOI: 10.1002/cphc.201500905
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Dynamics and Toxicity of a Cancer Drug in Proximity of Inorganic Nanoparticles under Visible Light

Abstract: Drug sensitization with various inorganic nanoparticles (NPs) has proved to be a promising and an emergent concept in the field of nanomedicine. Rose bengal (RB), a notable photosensitizer, triggers the formation of reactive oxygen species under green-light irradiation, and consequently, it induces cytotoxicity and cell death. In the present study, the effect of photoinduced dynamics of RB upon complexation with semiconductor zinc oxide NPs is explored. To accomplish this, we successfully synthesized nanohybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Several photosensitizers have been used for PDT for treating cancer due to their ability to induce ROS formation, which can cause cell death. 45 The efficacy of the substance depends on its physical and chemical characteristics, such as chemical purity, charge, solubility, distinct localization in cancer cells, residence, and accumulation time from drug administration. 45 RB is an anionic substance with low solubility in lipids which negatively affects its capability to cross biological membranes.…”
Section: Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several photosensitizers have been used for PDT for treating cancer due to their ability to induce ROS formation, which can cause cell death. 45 The efficacy of the substance depends on its physical and chemical characteristics, such as chemical purity, charge, solubility, distinct localization in cancer cells, residence, and accumulation time from drug administration. 45 RB is an anionic substance with low solubility in lipids which negatively affects its capability to cross biological membranes.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…51 Gianotti et al 52 and Uppal et al 53 developed organically modified silica nanoparticles with RB and showed phototoxicity on skin, 52 oral, and breast 53 cancer cells in vitro. Nanoparticles loaded with RB and made of different materials, such as ZnO 45 and PVP+Janus, 54 were studied, demonstrating greater ROS generation and toxicity in vitro and selectiveness for cancer cells, respectively.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Aer detailed photophysical characterization, ROS generation ability of the nanohybrid (FA-Mn 3 O 4 NP) was evaluated in vitro by monitoring the conversion of DCFH, a widely used marker for detection of ROS, to dichlorouorescein (DCF) in aqueous medium. 30 In presence of ROS, non-uorescent DCFH undergoes oxidation to produce orescent DCF (l ex ¼ 488 nm; l em ¼ 520 nm). So, we monitored the uorescence intensity of DCF at 520 nm (l ex ¼ 488 nm) with respect to time (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro ROS generation ability of the NPs and acid treated NPs were evaluated using DCFH-DA following a reported method without any modification [22]. Jobin Yvon Model Fluoromax-3 was used to measure the emission intensity.…”
Section: Methodsmentioning
confidence: 99%